Risk Factors for Coronary Artery Lesionsin Kawasaki Disease Independent of Antibiotic Use in Chinese Children - Lao, Sixian; Zhou, Tao; Kuo, Ho-Chang; Zhong, Guoping; Zeng, Weiwei (Frontiers in Public Health, 2022)
Objectives: To study the impact of antibiotics used in Kawasaki disease (KD) with coronary artery lesions (CAL) and identify independent risk factors. Methodology: This study reviewed the records of 287 KD patients between the years 2016 and 2020. Patients were grouped by their outcome, the CAL group, and a no-coronary artery lesions (NCAL) group, and stratified by the use of antibiotics. We collected clinical and laboratory data before the intravenous immunoglobulin (IVIG) treatment. Results: The two groups of KD patients with and without CAL were compared. The results showed that there are significant differences between groups which were erythrocyte count (p= 0.045) and hemoglobin (p =0.005), red blood cell-specific volume (p =0.001), immature granular cells percentage (p= 0.006), total protein (p= 0.045), albumin (p =0.041), alkaline phosphatase (p =0.023), and chlorine (p= 0.006). After multivariate logistic regression, neutrophil granulocyte percentage (odds ratio [OR]=1.200, 95% confidence interval [CI]: 1.008-1.428, p=0.040), lymphocyte percentage (p=0.028, OR =1.243, 95% CI: 1.024-1.508, p=0.028) and total protein (OR =4.414, 95% CI: 1.092-17.846, p=0.037) were found to be independent risk factors for CAL. After analyzing the cases with a history of antibiotic use, multivariate analysis showed no indicators were considered independent risk factors for CAL. Conclusion: Neutrophil granulocyte percentage, Lymphocyte percentage and total protein were independent risks for CAL in KD without antibiotics use history. The use of antibiotics affected physiological indicators of KD patients.